Human-centered assessment of robotics and exoskeletons in construction industry - Niehaus, Susanne; Erlebach, Rebecca; Rosen, Patricia Helen; Wischniewski, Sascha (Frontiers in Robotics and AI, 2025)
IntroductionRobotics and wearable systems are increasingly being discussed as potential solutions to address the physical demands, skill shortages and safety risks faced by the construction industry. However, their successful implementation hinges not only on technical feasibility, but also on their alignment with real working conditions. This article examines how interactive robotic systems and exoskeletons are experienced by construction workers by integrating macro-level data from European and national surveys with micro-level insights from pilot studies.MethodsFive large-scale European surveys were analysed and combined with data from four pilot studies involving 37 workers interacting with three robotic prototypes and one upper-body exoskeleton. Quantitative data included usability, workload, interaction principles and affinity for technology. Qualitative feedback was obtained through open-ended responses.ResultsA set of guidelines for a human-centred approach to inform policy were derived, offering practical guidance on designing and deploying interactive robotic systems that are functional, safe, acceptable and effective in changing work environments.DiscussionThe observed challenges highlight the gap between the early stages of system design and the realities of dynamic construction work, emphasising the need for a participatory, human-centred development approach. The findings suggest that a human-centred approach is essential for emerging technologies to be functional, safe, acceptable and effective in changing work environments.